Texture experimentation:: the (de) construction of artistic experiences with children (DAPesquisa, 2020)
This essay demonstrates the search for ways to reflect and write about the artistic experience called Texture Experimentation. This experiment was carried out in 2014 with children from 2 to 5 years old in a private school. The practice, which has distinct moments in its elaboration, gains strength when it comes out of the astonishment before the Chaos and assumes that a chaotic perspective could express the child's ways of re-elaborating his artistic work. Concepts emerged from the Chaos Theory, such as self-organization, unpredictability, complexity and systems are points of analysis, of (de) construction and re-elaboration of this experience carried out within the school space. The text is organized in blocks of ideas and text boxes: blocks that expose the central ideas of the practical process and text boxes with thoughts that express the practical path of artistic creation in the form of quotes, reports, narratives and images. This is a try to write in a less linear, more fragmented and open to the interpretations of readers way, thus bringing chaotic splashes also to the form of the text.
Keywords: Performing arts and children; Writing and art; Texture (Art)